More Than a Biological Condition: The Heteronormative Framing of Infertility - Maxwell, Erika; Mathews, Maria; Mulay, Shree (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
Infertility is often framed from the perspective of heterosexual couples, the dominant patient group using reproductive technologies. However, there are many types of patients availing of fertility treatments and those patients are often overlooked in policy, planning, service provision, and research. This commentary demonstrates the need for further research into LGBT subgroups, who frequently fall outside of infertility discourses, and are therefore especially disadvantaged by current policy and fertility service structures.